Addressing the Climate Crisis Local action in theory and practice - Howarth, Candice; Lane, Matthew; Slevin, Amanda (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book brings together a collection of cutting-edge insights into how action can and is already being taken against climate change at multiple levels of our societies, amidst growing calls for transformative and inclusive climate action. In an era of increasing recognition regarding climate and ecological breakdown, this book offers hope, inspiration and analyses for multi-level climate action, spanning varied communities, places, spaces, agents and disciplines, demonstrating how the energy and dynamism of local scales are a powerful resource in turning the tide. Interconnected yet conceptually distinct, the book's three sections span multiple levels of analysis, interrogating diverse perspectives and practices inherent to the vivid tapestry of climate action emerging locally, nationally and internationally. Delivered in collaboration with the UK's 'Place-Based Climate Action Network', chapters are drawn from a wide range of authors with varying backgrounds spread acrossacademia, policy and practice. Candice Howarth is Senior Policy Fellow at the LSE Grantham Research Institute and Co-director of the Place-based Climate Action Network (PCAN). She has an interdisciplinary background in climate policy, communication and pro-environmental behaviour with degrees in meteorology (BSc), climate change (MSc) and a Ph.D. in climate policy and pro-environmental behaviour. Matthew Lane is Researcher in Sustainable Urban Governance at the University of Edinburgh. His research focuses on how city and regional governments are coping with an increased responsibility to act on crises of sustainability despite having limited legal, institutional, political and economic capacity to do so. He has undertaken fieldwork in the UK, Zambia, China and the United States of America. Amanda Slevin is Environmental Sociologist with 20+ years' experience in community development, adult and community education. Co-Director of QUB's Centre for Sustainability, Equality and Climate Action, Amanda works with the Place-based Climate Action Network through which she co-founded Belfast Climate Commission and chairs its Community Climate Action Working Group.